Linguistic Skills in Bilingual Children With Developmental Language Disorders: A Pilot Study - Marini, Andrea; Sperindè, Paola; Ruta, Isabella; Savegnago, Christian; Avanzini, Francesco (Frontiers in Psychology, 2019)
The current pilot study compared the linguistic characteristics of a cohort of simultaneous bilingual children (Italian, L1; German L2) with developmental language disorders (DLDs) and those of bilingual peers with typical language development (TLD). Importantly, the two groups were balanced for a number of environmental variables (e.g., age of first exposure to the L2, acquisition contexts, degree of exposure to both languages) known to affect linguistic development in both TLD and DLD. The analyses included the assessment of the participants’ phonological short-term memory. Their lexical, grammatical and narrative abilities were analyzed in both languages by administering the Italian and German equivalent forms of the Battery for the assessment of language in children aged 4 to 12 - BVL_4-12 (Marini et al. 2015). The children with DLDs had reduced phonological short-term memory and lexical skills that, in turn, contributed to the reduced levels of local coherence and informativeness of their narratives. Such difficulties were found at similar levels in their two languages. These results suggest that reduced phonological short-term memory and lexical selection skills may reflect a core symptom in both mono- and bilingual children with developmental language disorders.